The Flourishing of Indonesian Conspicuous Consumption in the Digital World and Its Effects on the Evolution of Hijrah Movements - Masni, Melly (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study explores the intersection of conspicuous consumption and the Hijrah movement within Indonesia's socio-cultural and economic transformations. The rise of the middle class, coupled with the proliferation of social media, has amplified conspicuous consumption, where symbols of wealth and social status are prominently displayed. In this context, religiosity emerges as a unique form of status signaling, referred to in this study as